Political Economy of Discretionary Allocation of Annual Development Programmes: Theory and Evidence from Balochistan (The Pakistan Development Review, 2025)
This article discusses and analyses the presence of discretionary allocations of annual development programmes (ADP)—the annual development budget—in the Balochistan province of Pakistan. The paper builds a strong theory and uses robust empirical techniques to assess how the political and bureaucratic elite discretionarily and disproportionally allocates the development funds to meet two central objectives: First, to allow misappropriation of the development funds to their benefit; and second, to make constituency/district-specific allocations to buy political allegiance, indulge in pork-barrel and promote patronage politics— clientelism. For empirical assessment, the article applies an unbalanced panel dataset for districts from the provincial level sources. The theoretical propositions and the empirical results show a presence of discretion and clientelism in the process of budget making and projects’ allocation to districts/constituencies, for incumbent politicians and senior career officials in charge of the budgetary-making process make disproportionate budgetary allocations in ADP to their home districts or constituencies or the projects with leverage of extraction and kickbacks in the process of allocations, bidding, and execution. It is evident that constituencies or districts, without representation in the government/cabinet and/or senior bureaucracy in the ministries that make public policy, receive far lesser budgetary allocations than their proportionate share, notwithstanding their prevailing poor social and economic landscape. Such discretionary allocations suffice personal interests and support clientelism in resource sharing, creating inter-regions and inter-districts/constituencies disparity in terms of economic and social development within the province.